2015
DOI: 10.1002/admi.201500046
|View full text |Cite
|
Sign up to set email alerts
|

Significant Capacity and Cycle‐Life Improvement of Lithium‐Ion Batteries through Ultrathin Conductive Film Stabilized Cathode Particles

Abstract: Figure 6 in this manuscript was published without the corresponding equivalent circuit (Figure 6c). The corrected version including Figure 6c is below. CORRECTION Figure 6. Electrochemical impedance spectra at 3.8 V for a) UC and various oxides coated LiMn 2 O 4 with 0 th cycle at room temperature, b) higher frequency (10 MHz to 1Hz) semicircle region, and c) equivalent circuit fi t for the impedance spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
43
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 47 publications
2
43
2
Order By: Relevance
“…In our recent study, we employed the use of optimally thick CeO 2 film prepared by ALD on LiMn 2 O 4 particles, which showed a 24% increase in initial capacity and 95% capacity retention, when tested at a 1C rate for 1,000 cycles at room temperature. 30 In addition to that, the conductive effects of CeO 2 ALD films were studied and compared with uncoated substrates and insulating coating materials. 31 We found that the ceria ALD coated material showed much improved ionic and electronic conductivities, as compared to the Al 2 O 3 and ZrO 2 ALD coated LiMn 2 O 4 samples.…”
mentioning
confidence: 99%
“…In our recent study, we employed the use of optimally thick CeO 2 film prepared by ALD on LiMn 2 O 4 particles, which showed a 24% increase in initial capacity and 95% capacity retention, when tested at a 1C rate for 1,000 cycles at room temperature. 30 In addition to that, the conductive effects of CeO 2 ALD films were studied and compared with uncoated substrates and insulating coating materials. 31 We found that the ceria ALD coated material showed much improved ionic and electronic conductivities, as compared to the Al 2 O 3 and ZrO 2 ALD coated LiMn 2 O 4 samples.…”
mentioning
confidence: 99%
“…ALD ensures control of film thickness at nanometer level. However, if the ALD film is insulating, such trade-off still exists14, which has also been demonstrated in our recent work and an effective solution was proposed17. It has been demonstrated that coating an optimal thickness of conductive metal oxide films could improve both specific capacity and cycling performance.…”
mentioning
confidence: 51%
“…As learned from our previous work17, the drawback of coating on particles is slower species transport. Consequently, a demonstration of performance improvement via ALD coatings at a high C rate is significant because the diffusivity of ions in the solid phase becomes significant as the input current increases.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations